2018
DOI: 10.18433/jpps29856
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Doses of Eltrombopag do not Inhibit Hepatic BCRP in Healthy Volunteers: Intravenous Ceftriaxone as a Model

Abstract: The results do not support the existence of a clinical pharmacokinetic drug interaction involving hepatic BCRP in human subjects receiving intravenous ceftriaxone and oral eltrombopag. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Cefuroxime also showed a great variation in protein binding in critically ill patients (0.25%–72.64%) ( van Raaij et al, 2020 ). As mentioned earlier, patients on hemodialysis showed lower protein binding (8%) for ceftriaxone compared to healthy volunteers (protein binding 90%–95%) ( Stoeckel et al, 1984 ; Matzke et al, 2000b ; Neves et al, 2018 ; Herrera-Hidalgo et al, 2020 ). This was also seen for cefepime in patients on continuous venovenous hemofiltration and continuous venovenous hemodialysis.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Cefuroxime also showed a great variation in protein binding in critically ill patients (0.25%–72.64%) ( van Raaij et al, 2020 ). As mentioned earlier, patients on hemodialysis showed lower protein binding (8%) for ceftriaxone compared to healthy volunteers (protein binding 90%–95%) ( Stoeckel et al, 1984 ; Matzke et al, 2000b ; Neves et al, 2018 ; Herrera-Hidalgo et al, 2020 ). This was also seen for cefepime in patients on continuous venovenous hemofiltration and continuous venovenous hemodialysis.…”
Section: Discussionsupporting
confidence: 53%
“…This was confirmed for cefazolin, which was bound for mean 72.3% in cirrhotic patients ( Ohashi et al, 1986 ). Also for ceftriaxone protein binding was lower (83.9% vs. 90%–93% in healthy volunteers) ( Stoeckel et al, 1984 ; Mimoz et al, 2000 ; Neves et al, 2018 ; Herrera-Hidalgo et al, 2020 ) as well as for cefpiramide (89.6 vs. 98.1 in healthy volunteers) ( Demotes-Mainard et al, 1991 ). For cefalothin there was not a significant difference in protein binding between patients with cirrhosis (73.4%) and controls (75.9%) ( Ohashi et al, 1986 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have shown that different efflux transporters are expressed in alveolar epithelial cells of human, including P-glycoprotein, multidrug-resistance-associated protein 1 (MRP1), and breast cancer resistance protein. 17 Also, ceftriaxone is a substrate of multidrug-resistance-associated protein 2 and breast cancer resistance protein 18 and can block the P-glycoprotein function. 19 These factors may be related to the high penetration and require further study.…”
Section: Discussionmentioning
confidence: 99%